Ukrainian Scholars’ Pilot Research in Primary Education: Leveling Classes (1975–1982) - Tetiana Havrylenko (Pedagogical Discourse, 2015)
The article deals with one of the pilot researches carried out by Ukrainian scholars in primary education in the second half of the 70-s – the first half of the 80-s of the 20th century. The author focuses on the organizational aspects and results of the experiment, the purpose of which was to check the reasonability and effectiveness of leveling classes as a form which makes it possible to cope with junior pupils’ poor progress. It is shown that research assistants of Pedagogics and Psychology Research Institute of the Ukrainian SSR (M.V.Bohdanovych, Y.Z.Hilbukh, A.P.Koval, H.F.Kumarina, N.F.Skrypchenko etc.) played an important role in planning, organization and realization of this research. It was found out that during the first stage of the experiment (1975–1979) carried out in schools of the Donetsk region scholars defined the following optimal conditions for pupils lagging behind in leveling classes: the number of pupils, functioning of extended-day groups within classes, slow pace of training, adaptation of lesson structure to pupils’ cognition, mastering material mainly during lessons, absence of additional classes, assessment of pupils’ achievements only, creating a relaxed and friendly atmosphere in the process of training and education etc. It is established that during the second stage of the experiment (1979–1982) carried out in schools in all regional centers of the Ukrainian SSR the following factors which positively influenced the training, education and development of pupils in leveling classes were determined: the relative homogeneity of pupils, the ability to operate time, mobilization of highly skilled and trained teachers etc. It is manifested that the results of the long-term pilot research have shown high efficiency of a new form of training concerning coping with educational problems and preventing poor progress of junior pupils. That is why they became widespread in the sphere of school practice of the Ukrainian SSR starting from 1983.